2018
DOI: 10.1029/2018gb005941
|View full text |Cite
|
Sign up to set email alerts
|

Blue Carbon Storage Capacity of Temperate Eelgrass (Zostera marina) Meadows

Abstract: Despite the importance of coastal ecosystems for the global carbon budgets, knowledge of their carbon storage capacity and the factors driving variability in storage capacity is still limited. Here we provide an estimate on the magnitude and variability of carbon stocks within a widely distributed marine foundation species throughout its distribution area in temperate Northern Hemisphere. We sampled 54 eelgrass (Zostera marina) meadows, spread across eight ocean margins and 36° of latitude, to determine abioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
148
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 141 publications
(194 citation statements)
references
References 119 publications
(214 reference statements)
33
148
5
Order By: Relevance
“…The highest sediment OC content was found in Southeast Alaska and South Slough, Oregon, while the lowest values were found in the Southern Salish Sea (Figure ). As such, we did not identify a latitudinal trend in the data, consistent with Röhr et al (), who found that latitude explained relatively little variation in OC stocks in Z. marina meadows across the Northern Hemisphere. For example, although the highest %OC values were measured in Alaska (2.32%), some sites in Alaska also had very low values (0.09%).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The highest sediment OC content was found in Southeast Alaska and South Slough, Oregon, while the lowest values were found in the Southern Salish Sea (Figure ). As such, we did not identify a latitudinal trend in the data, consistent with Röhr et al (), who found that latitude explained relatively little variation in OC stocks in Z. marina meadows across the Northern Hemisphere. For example, although the highest %OC values were measured in Alaska (2.32%), some sites in Alaska also had very low values (0.09%).…”
Section: Discussionsupporting
confidence: 91%
“…The sediment carbon content values reported here fall within the range of those reported from other temperate Z. marina meadows globally. The mean OC content for the entire Pacific Northwest region (0.7%) is within the range of values reported from eelgrass meadows in the Black Sea (0.2%), Portugal (0.6%), and the Baltic Coast of Sweden (0.2%; Dahl et al, ), albeit slightly lower than the average value of 1.4% reported from Z. marina across the globe (Röhr et al, ) and the Gullmarn Fjord in Sweden (2.8%; Dahl et al, ). Our PNW values also align with those reported from meadows on the Atlantic coast of North America of 0.4% (Greiner et al, ) as well as from Denmark (1.7%) and Finland (0.2%; Röhr et al, ).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations